Agriculture for nutrition in latin America and the Caribbean : from quantity to quality - Instituto Interamericano de Cooperación para la Agricultura (IICA) (The World Bank, 2022)
The challenge is how to bridge the gap that exists in our region between being an agricultural powerhouse and yet having to address the nutrition problems of the very households that produce the food. The new challenge of integrating nutrition and agriculture must be achievable with political leadership and inter-institutional coordination. This Guidance Note seeks to close some of the important knowledge gaps on how best to identify, design, implement, monitor and evaluate agriculture and food security interventions. It encourages critical thinking and careful planning for sustainable solutions that address the challenges of linking agriculture with nutrition interventions.